Redesign of the UI/UX of the Klik Indomaret Application using Design Thinking and System Usability Scale - Iin Nurul Latifah; Firman Noor Hasan (SISTEMASI, 2026)
The development of e-commerce encourages retail companies to provide digital services that offer a better user experience. However, observations and user review analysis indicate that the Klik Indomaret application still has several issues, including the absence of an order cancellation feature, a chat feature with stores, and integrated communication with delivery drivers, which affect the application's usability. This study aims to redesign the User Interface (UI) and User Experience (UX) of the Klik Indomaret application using the Design Thinking method and evaluate the redesigned interface using the System Usability Scale (SUS). Data were collected through observation, user review analysis on the Google Play Store and App Store, and questionnaires distributed to 60 participants. The redesign process consisted of the empathize, define, ideate, prototype, and testing stages, followed by a SUS evaluation involving 30 participants. The results showed that the average SUS score increased from 42.04 before the redesign to 77.58 after the redesign, representing an improvement of 35.54 points. These findings indicate that the redesign improved the application's usability and produced a design that better meets user needs. The findings are expected to serve as a reference for developing more user-centric retail e-commerce applications through features that enhance digital service quality and overall user experience.